COMPETITIVENESS OF KNOWLEDGE-BASED ECONOMIES. SUGGESTION FOR MEASURING - Madrak-Grochowska, Małgorzata (Ekonomia i Prawo. Economics and Law, 2013)
The present paper focuses on a presentation of four pillars of knowledge, occurring as the sources of competitive advantage for knowledge-based economies, and on the construction of taxonomic measure for assessing competitiveness’ degree of 29 this type economies in 2000-2010. To build this taxonomic measure, author used 21 diagnostic variables representing four areas of knowledge-based economies’ competitiveness, i.e. the system of economic incentives and institutional regime, well educated and entrepreneurial society, the innovation system and the information and communication infrastructure. The results of these empirical analyses led to create rankings of knowledge-based economies’ competitiveness and led to the conclusion that in 2000-2010 the average level of knowledge-based economies’ competitiveness has grown steadily, and the scope of its volatility has been significantly reduced.